PROFIL PERESEPAN OBAT PADA PASIEN RAWAT JALAN JAMKESDA DARI POLI KARDIOVASKULAR DI APOTEK RUMAH SAKIT LABUANG BAJI MAKASSAR PERIODE JANUARI – JUNI 2014 - Olii, Audi Triani; Nurlina, Nurlina; Niswah, Hilyatun (Jurnal Ilmiah As-Syifaa, 2014)
Study of Drugs Prescribing Profile In Outpatient Jamkesda of Poly Cardiovaskular In Labuang Baji Hospital Makassar period January ? June 2014 has done. The aim of this study is to obtain the secondary data and than  analyzing themby administration screening, pharmaceutical screening and clinical screening. This study was descriptive type with retrospective data which taken from secondary data on Outpatient Jamkesda of Poly Cardiovaskular In Labuang Baji Hospital Makassar period January ? June 2014. Based on the results of this study, concluded that from 5617 of prescription sheets of Jamksda outpatient were included in the study period, 508 sheets recipe comes from Cardiovascular Poly (9%) which 52,4% from that recipe is male patients,  32,1% are 51-60 years, 89,2% without doctor?s initials, 23,2% of  prescription contain 5 different drugs, 74,8% of  prescription contain  diuretics as the first choice of therapy, and there is a 1133 cases of drug interaction cases. Key words : Prescribing Profile, Cardiovascular, Screening Recipe.